Unpacking the Form and Structure of Jaya Baya Music Composition in JES Gamelan Fusion - I Putu Riangga Budi Pramana; Hendra Santosa; I Saptono; I Gede Yudarta; I Wayan Sutirtha (Universitas Negeri Medan, 2023)
This paper aims to reveal the structure and form of Jaya Baya music composition by I Nyoman Windha in JES Gamelan Fusion. Jaya Baya's Music Composition in JES Gamelan Fusion is the result of a rearrangement of the same title worked on with the Sekar Jaya Gamelan Group using Angklung gamelan in 2002 by taking the idea of revealing the meaning of the Bom Bali I Tragedy. This research uses qualitative descriptive research methods, with musicological approach procedures, to analyze the form and structure of the Composition of Musik Jaya Baya in JES Gamelan Fusion. This music turnover is in the style of fusion music, by combining the values of Bali characteristics with Western music values presented by JGF (Jes Gamelan Fusion). It turns out that in her composition, Windha is still thick with Balinese karawitan practices, where various elements of music, the practice of music playing techniques, ornamentation, and even the structure of the music are still Balinese style. Two types of gamelan as the basic foundation of music fusion, namely Jegog gamelan and Semar Pagulingan Saih Pitu gamelan, have certainly given rise to sound color perspectives and instrumentation techniques as a creative force for composition creation. Windha has also made hybrid music in a fusion style which turned out to be an alternative to combining Western and Eastern music (Nusantara).